Pengaruh Brand Ambassador, Kualitas Website dan Keragaman Produk terhadap Keputusan Pembelian pada E-Commerce Shopee di Jakarta - Fifi Mirajna; Yugi Setyarko (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to analyze the impact of Brand Ambassador, Website Quality, and Product Variety on Purchase Decisions in Shopee E-Commerce in Jakarta. The data used in this study is primary data obtained through the distribution of questionnaires to Shopee users in Jakarta. The sampling technique used is Non-Probability Sampling, with the method being Accidental Sampling. The sample size taken was 103 respondents based on the Lemeshow formula. This study focuses on three key variables that are believed to have a significant impact on consumer purchase decisions. Brand Ambassador refers to public figures or celebrities who represent a particular brand and can influence consumers' perceptions of the products offered. The role of a Brand Ambassador is crucial because it can enhance the attractiveness and credibility of a product in the eyes of consumers. Website Quality includes aspects such as design, navigation, loading speed, and user-friendliness while shopping. A website that is easy to use, fast, and visually appealing will enhance user satisfaction, which in turn can encourage purchasing decisions. Product Variety is related to the range of products available on the e-commerce platform, offering consumers more choices to meet their needs. The more varied the products offered, the higher the likelihood that consumers will make a purchase. The analysis tool used in this study is SPSS version 26 for regression analysis. The research findings show that Brand Ambassador, Website Quality, and Product Variety have a significant effect on Purchase Decisions in Shopee E-Commerce in Jakarta. An attractive Brand Ambassador, a high-quality website, and a wide variety of products have been proven to influence consumers’ purchase decisions. These findings indicate that Shopee E-Commerce needs to continuously improve these factors to enhance consumer experience, strengthen loyalty, and increase sales.